(3TQM GdSjQ GdcHjQs - (3CHh HcQ eMeO Hf GHi Sgd GdSQNSis; (3eMeO GdTjHGfj , eMeO Hf GdMSf GdTjHGfj, GdTjHGfjs
(3ChdgG (B:s
(3jHOC HHGH GdTQcI ai GdZfjeI s
(3BNQgG (B:s
(3jfJgi HHGH GdYHO jYJb HESdGeg s
(3GdfSNI HgG MhGTs
(3Ydjg SeGYGJ SfI (B676(3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B194s
Keywords: (3Gdabg GdMfajs